Empathy: the ability to illuminate interpesonal relationships: a study among children in São Paulo state public schools - Boni, Larissa Di Genova [UNESP]; Farhat, Fernanda Issa de Barros[UNESP]; Moreno, Cecilia Beatriz (Unesp-faculdade Ciencias & Letras, 2022)
This article presents a descriptive research that included the participation of children, students from two directorates of the Sao Paulo state public education network: the DRE Leste 3 in the metropolitan region of Sao Paulo, with 824 respondents, and the DRE of Taquaritinga, in Sao Paulo's countryside, with 225 children who responded to the survey, totaling 1049 participants. The objective was to identify the the levels of empathy pointed out by students in the initial years. For this, we used a questionnaire with closed questions, divided into two parts: in the first, containing 13 questions, we seek to identify the the student's profile and, in the second, with eight questions, we aim to visualize the levels of empathy. The questionnaire was built by members of the GEPEM - Group of Studies and Research in Moral Education from the current literature. The students responded online, through a Google Forms form. The results indicated how much children indicate that they are able to be sensitized to the feelings of their peers and show that self-control is still under construction at this stage of development among the children participating in the investigation.
Keywords: Empathy; Children; Caring environment; Ethical school life